Increasing the competitiveness of corn into healthy noodles for Rantau Bengkayang Village, West Kalimantan - Yohana Sutiknyawati Kusuma Dewi; Widadi Padmarsari Soetignya; Rahmidiyani (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2022)
Rantau village is a village that is not yet food secure in the Bengkayang district. Corn is one of the main village products but still uses conventional cultivation methods and has not implemented farming management, so its utilisation is not optimal. The crop yields in the form of shelled corn are sold to Singkawang at a price of IDR 4000 per kg. Lack of knowledge and skills, including corn diversification technology, is the reason why this village is not yet developed. The impact is that the use of corn to increase household food consumption patterns has not been carried out. One of the partners of this service program is the dissemination of technology to the community, one of which is PKK. The purpose of this service is to increase the knowledge and skills of PKK members so that they are able to improve food consumption patterns and initiate new income for families. The solution is to transfer processed diversification technology that is applied to food products, namely healthy noodles from corn and vegetables. Implementation methods include socialisation, technology dissemination, evaluation and monitoring. The target of this service is for at least 50% of PKK members to increase their knowledge of healthy noodles, apply noodle menus for social events, at least 3 PKK members and application for family food security, and at least 1 PKK member initiates commercialisation around the village.